Developmental issues of web-based decision support system - Fadhilah, Ahmad; Noraziah, Ahmad; Suhailan, Safei; Azrul Amri, Bharun Abidin; Abdalla, Ahmed N.; Aznida Hayati, Zakaria Mohamad (Asian Network for Scientific Information, 2012)
Decision Support Systems (DSS) are computer programs that aid users in a problem solving or decision-making environment. DSS contains decision making information and other related data that may be of interest to unscrupulous competitors and stakeholders. Therefore, a DSS that is developed for web-based environment has to be secured from unauthorized access or malicious attacks. This study describes a framework of a secured DSS suitable to support decision making activities. Security issues are discussed from various perspectives with the proposed mechanisms to ensure a secured DSS implementation in distributed environment. Issues in web-based application development that include data growth, system performance and appearance compatibility are also presented together with their proposed solutions. Considering security and development issues could contribute towards successful implementation in the decision making process.